Studi Kegagalan Struktur Dan Perbaikan Gedung Pusat Jantung Regional (PJR) Rsud M. Jamil Padang Pasca Gempa 30 September 2009 - Arman A (Jurnal Momentum ISSN 1693-752X)
Padang City is an area that suffered considerable damage and great material losses in the earthquake of 2009, one of the buildings that suffered severe damage to both structural damage and non-structural is building the Regional Heart Center (PJR). So that needs to be analyzed the causes of damage to the structure of the building column. To find out the cause of damage to the column was done evaluation of existing buildings visually and compared with analysis of building structures using ETABS program. Results of analysis of existing conditions of the building is visually found that there was damage to the structural columns of the building collapse was the result of analysis of structural columns in the building suffered flexural and shear. From the visual results and analysis can be concluded that the structure of column building collapse caused by the earthquake and must be given strong reinforcement for the building to receive the load mainly by the quake.